2020
DOI: 10.1016/j.isci.2020.101887
|View full text |Cite|
|
Sign up to set email alerts
|

Dimeric Transmembrane Orientations of APP/C99 Regulate γ-Secretase Processing Line Impacting Signaling and Oligomerization

Abstract: Summary Amyloid precursor protein (APP) cleavage by the β-secretase produces the C99 transmembrane (TM) protein, which contains three dimerization-inducing Gly-x-x-x-Gly motifs. We demonstrate that dimeric C99 TM orientations regulate the precise cleavage lines by γ-secretase. Of all possible dimeric orientations imposed by a coiled-coil to the C99 TM domain, the dimer containing the 33 Gly-x-x-x-Gly 37 motif in the interface promoted the Aβ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 50 publications
3
21
0
Order By: Relevance
“…Importantly, extracellular monomeric Aβ was found exclusively in the soluble proteins fraction while hexameric Aβ was confined exclusively in vesicles (Fig. 4c), in agreement with the recent observations on "Aβ-like" oligomeric species [44]. To note, EVs size distribution was similar between all conditions but the number of EVs was higher in PS1-KD and PS2-KD as compared to respective controls (Fig.…”
Section: Cellular Pathways and Contribution Of Presenilins To The Formation Of Hexameric-like Aβ Assembliessupporting
confidence: 91%
“…Importantly, extracellular monomeric Aβ was found exclusively in the soluble proteins fraction while hexameric Aβ was confined exclusively in vesicles (Fig. 4c), in agreement with the recent observations on "Aβ-like" oligomeric species [44]. To note, EVs size distribution was similar between all conditions but the number of EVs was higher in PS1-KD and PS2-KD as compared to respective controls (Fig.…”
Section: Cellular Pathways and Contribution Of Presenilins To The Formation Of Hexameric-like Aβ Assembliessupporting
confidence: 91%
“…Using a system in which dimerization is imposed from the intracellular domain, Eggert and colleagues observed that controlled dimerization resulted in decreased Aβ generation [105]. But more recently, the acquisition of the cryo-EM structure of 𝛾-secretase in complex with C83 hinted that processing of C-terminal fragments (CTF) could indeed not occur in their dimeric form [106], in line with our own observations using a cell-free 𝛾-secretase processing assay [96]. A first answer to these apparently contradicting observations was provided by our finding that GxxxG motifs were critical in regulating the orientations of TM dimerization and that a specific interface was required for amyloidogenic processing [90].…”
Section: Transmembrane Interactions and Amyloidogenic Processingsupporting
confidence: 62%
“…A first answer to these apparently contradicting observations was provided by our finding that GxxxG motifs were critical in regulating the orientations of TM dimerization and that a specific interface was required for amyloidogenic processing [90]. Using a system of fusion proteins that force dimerization of TM helices in all possible orientations, we demonstrated that precise dimeric orientations of C99 controlled 𝛾-secretase processing by regulating the initial 𝜀cleavage and therefore influencing AICD-dependent signaling and generation of Aβ42 [96]. Noteworthy, the dimeric orientation resulting in enhanced Aβ42 production and AICD-dependent signaling contained GxxxG motifs in the interface, but unfolding is mandatory for γ-processing since covalently bound APP CTFs are not further processed [96].…”
Section: Transmembrane Interactions and Amyloidogenic Processingmentioning
confidence: 98%
See 1 more Smart Citation
“…To clarify how the CBS regulates APP processing, we produced seven single mutants in the APP 751 protein either in the juxtamembrane region at aa positions 22, 26, and 28 of the Aβ sequence (positions 674, 678, and 680 of APP 751 ) that exhibited the greatest chemical shift perturbation in response to cholesterol in NMR studies [ 23 ] or in the TMD at aa positions 29, 33, and 39 (positions 681, 685 and 691 of APP 751 ) involved in APP dimerization and orientation [ 26 ]. In addition, two double mutants, 26/28 and 29/33, were constructed.…”
Section: Introductionmentioning
confidence: 99%